Consumer Satisfaction with Chill Coffee Gubuklakah Evaluated via Customer Experience, Brand Ambassadorship, and Store Atmosphere - Wenny Eka Prasetiawan; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardhana (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to identify the influence of Customer Experience, Brand Ambassador and Store Atmosphere on Consumer Decisions among Chill Coffee Gubuklakah consumers. The sample used in this research used the Malhotra formula which had a sample size of 75 respondents who could represent consumers of Chill Coffee. The results of this research show that the influence of Customer Experience, Brand Ambassador and Store Atmosphere simultaneously has a positive and significant effect on consumer decisions. There is a partial influence between the Customer Experience variable on consumer decisions for Chill Coffee Gubuklakah consumers. However, the Brand Ambassador and Store Atmosphere variables do not partially influence the consumer decision variables of Chill Coffee Gubuklakah consumers.